Mandaluyong business directory 1992-1993. (Mandaluyong, Metro Manila Kilter Enterprises, 1993)
Considered as an important medium through which new products, services and technologies offered by businesses in Mandaluyong can be showcased to generate greater public interest, investment and utility, and the development of Mandaluyong as a strategic investment center in Manila. This directory lists companies alphabetically according to their products and services. That directory also features some facts about the city: distribution of establishments, commercial and industrial areas, statements of annual revenues, local banks, schools, hospitals, and a directory of the different departments of the Municipality of Mandaluyong.
The 1992-1993 Mandaluyong Business Directory "serves as an important Medium through which new products, services and technologies offered by business in Mandaluyong can be showcased to generate greater public interest, investments and utility". this 263 pages publication includes an amended copy of the Mandaluyong Business Tax Code of 1991; copies of business-related municipal ordinances enacted by the 1998-1999 Snggunian Bayan of Mandaluyong, business listings, taxpayers guidelines, and copy of the local government code.
Keywords: Business enterprises -- Philippines -- Mandaluyong -- Directories; Business -- Philippines -- Mandaluyong; Mandaluyong City -- Economic conditions